Adolescent health and well‐being in sub‐Saharan Africa: Strengthening knowledge base and research capacity through a collaborative multi‐country school‐based study - Sachin Shinde; Ramadhani Abdallah Noor; Mary Mwanyika‐Sando; Mosa Moshabela; Amare W. Tadesse; Huda Sherfi; Alain Vandormael; Tara Young; Amani Tinkasimile; Roisin Drysdale; Till Baernighausen; Deepika Sharma; et al. (Maternal and Child Nutrition)
Abstract In Sub‐Saharan Africa (SSA), adolescents make up around one‐quarter of the population who are growing up in a rapidly urbanizing environment, with its associated risks and benefits, including impacts on health, psychosocial development, nutrition, and education. However, research on adolescents' health and well‐being in SSA is limited. The ARISE (African Research, Implementation Science and Education) Network's Adolescent Health and Nutrition Study is an exploratory, school‐based study of 4988 urban adolescents from five countries: Burkina Faso, Ethiopia, South Africa, Sudan, and Tanzania. A multistage random sampling strategy was used to select the schools and adolescents. Adolescent boys and girls aged 10–15 years were interviewed using a standardized questionnaire by trained enumerators. The questionnaire covered multiple domains including demographic and socioeconomic characteristics, water, sanitation and hygiene practices, antimicrobial resistance, physical activity, dietary behaviours, socioemotional development, educational outcomes, media use, mental health, and menstrual hygiene (only for girls). Additionally, a desk review of health and school meal policies and programs and a qualitative investigation into health and food environments in schools were conducted with students, administrators, and food vendors. In this paper, we describe the study design and questionnaire, present profiles of young adolescents who participated in the study, and share field experiences and lessons learned for future studies. We expect that this study along with other ARISE Network projects will be a first step toward understanding young people's health risks and disease burdens, identifying opportunities for interventions and improving policies, as well as developing potential research capacities on adolescent health and well‐being in the SSA region.